Design of a Sampling System for Wide Range nano-current Signal. Issue 1 (1st October 2022) - Zheng, Sha; Shi, Junbiao; Chen, Yonggang; Gui, Peng; Liu, Wenyang; Guo, Shuai; Zhang, Yuhuan
Abstract: Space particle radiation will greatly shorten the service life of basic components, resulting in premature failure of aircraft. For newly developed electronic components for space applications, strict anti irradiation performance evaluation must be carried out to master their working characteristics and performance degradation mechanism in space irradiation environment, so as to provide a reliable guarantee for the safe operation of aerospace electronic equipment in orbit. Taking high-voltage power devices such as SiC MOSFET and IGBT as the research object, this paper designs a high-precision weak current signal acquisition and measurement system to continuously monitor its working current under specific track applications, so as to verify the mechanism of space radiation effect and the effectiveness of reinforcement technology. The experimental results show that the system has the advantages of wide range, low noise, high precision and good stability. It can be applied to the experimental verification of high-voltage power devices in various space environments, including space station orbit.